Access to vocational training in three sectors of the European economy - Lassibille, Gérard [Verfasser]; Paul, Jean-Jacques [Verfasser] (My University, 1996)
This report presents findings of a study of the theoretical and practical methods of access to continuing vocational training. It summarizes six reports that compare the following: the construction sector in Spain, France, Italy, and Luxembourg; the banking, insurance, commerce, and administration sectors in Germany, Ireland, the Netherlands, and the United Kingdom; and the electricity and electronics sector in Belgium, Denmark, Greece, and Portugal. Part I uses a common approach to examine practices in each sector. Section 1 provides an overview of general background aspects such as economic features and the national legal framework for continuing training. Section 2 examines organization of continuing training: agreements between the social partners, initial training of employees, and role played by partners in the organization of continuing training. Section 3 examines continuing training practices, separating access to training from its actual conduct, validation, and links with careers. Part II draws conclusions and determines whether any sectoral practices actually exist. It reports that the construction sector seems fairly well organized; the banking and insurance sector has a well-structured training system; but continuing training seems less structured in the electricity and electronics sector. It also delineates the methodological limits of the approach and lays the foundations for a new framework for analyzing access to continuing vocational training. (BIBB-Doku)
Keywords: S 1.5.2 Berufliche Weiterbildung; G 1.2.3.2 Anforderungen & Bedarfe; G 1.2.4.1.6 Baugewerbe; G 1.2.4.2.4 Kredit und Versicherung; G 1.2.4.2.6 Öffentliche Verwaltung, Verteidigung, Sozialversicherung; G 1.2.4.1.5 Energie- und Wasserversorgung; I 2.2 Europa; Berufliche Weiterbildung; Zugangsvoraussetzung; Qualifikationsanforderung; Wirtschaftssektor; Baugewerbe; Finanzwirtschaft; Versicherungsgewerbe; Verwaltung; Energiewirtschaft; Internationaler Vergleich; Europäische Union